h - Noble, James; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 26th European Conference on Object-Oriented Programming, ECOOP 2012, held in Beijing, China, in June 2012. The 27 revised full papers presented together with two keynote lectures were carefully reviewed and selected from a total of 140 submissions. The papers are organized in topical sections on extensibility, language evaluation, ownership and initialisation, language features, special-purpose analyses, javascript, hardcore theory, modularity, updates and interference, general-purpose analyses.
Keywords: Computer science; Computer Communication Networks; Software engineering; Logic design; Computer Science; Programming Techniques; Software Engineering; Programming Languages, Compilers, Interpreters; Logics and Meanings of Programs; Mathematical Logic and Formal Languages; Computer Communication Networks